2020
DOI: 10.3389/fpls.2020.00675
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Role of Nitric Oxide in Phytotoxicity-Mitigation of Copper

Abstract: Phytotoxicity of metals significantly contributes to the major loss in agricultural productivity. Among all the metals, copper (Cu) is one of essential metals, where it exhibits toxicity only at its supra-optimal level. Elevated Cu levels affect plants developmental processes from initiation of seed germination to the senescence, photosynthetic functions, growth and productivity. The use of plant growth regulators/phytohormones and other signaling molecules is one of major approaches for reversing Cu-toxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 195 publications
(259 reference statements)
0
20
0
Order By: Relevance
“…However, the effectiveness of H 2 O 2 combined with S has not been reported earlier. (Sade et al, 2011;Fatma et al, 2016;Sehar et al, 2019;Rather et al, 2020aRather et al, , 2020bAsgher et al, 2021 (Khan et al, 2014;Sun et al, 2016;Shan et al, 2018;Li et al, 2020;Asgher et al, 2021). Xu et al (2011) also showed the involvement of the enzymes of the ascorbateglutathine cycle in protection of Kentucky bluegrass to drought damage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the effectiveness of H 2 O 2 combined with S has not been reported earlier. (Sade et al, 2011;Fatma et al, 2016;Sehar et al, 2019;Rather et al, 2020aRather et al, , 2020bAsgher et al, 2021 (Khan et al, 2014;Sun et al, 2016;Shan et al, 2018;Li et al, 2020;Asgher et al, 2021). Xu et al (2011) also showed the involvement of the enzymes of the ascorbateglutathine cycle in protection of Kentucky bluegrass to drought damage.…”
Section: Discussionmentioning
confidence: 99%
“…Drought stress increased ROS and ABA contents in plants (Liu et al ., 2019), but supplementation of H 2 O 2 and S decreased the oxidative stress by increasing the activity of antioxidant enzymes. It is evident from previous reports that various abiotic stress factors such as drought, salt, and heavy metal stress lead to an increase in the activity of antioxidant enzymes and a decrease of ROS (Sade et al ., 2011; Fatma et al ., 2016; Sehar et al ., 2019; Rather et al ., 2020a, 2020b; Asgher et al ., 2021). In the present study, our results also suggest that both H 2 O 2 and S coordinately participate in upregulating the activity of antioxidant enzymes to decrease lipid peroxidation observed as content of H 2 O 2 and TBARS in leaves under drought stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, buildup of heavy metals in the rooting medium would significantly retard plant growth; elicit perturbations in cellular metabolism; affect the uptake of potassium, calcium, and magnesium; and decrease the number of flowers, fruits, and crop yield. The most common toxicity symptoms in plants are necrosis, chlorosis, wilting, and disturbance of physiological processes, including photosynthesis, transport of photo-assimilates, mineral nutrition, and plant structure damage ( Kasprzak et al, 2003 ; Rather et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%